(untitled) (Bangladesh Journal of Botany, 2021)
Epimedium brevicornu Maxim. rich in flavonoids is used as a medicinal plant. The purpose of this study was to predict the adaptive zones, and quality zones, provide experimental data support for the development and utilization of E. brevicornu. ArcGIS was used to extract environmental factors associated with E. brevicornu, SPSS was used to analyze the correlation between the icariin content and these environmental factors. In the end, the quality zoning was performed based on the icariin contents of collected samples. A significant negative correlation between the July vapor pressure and the icariin content was observed. Quality E. brevicornu was mainly distributed in parts of Shanxi, Shaanxi, Gansu. The icariin contents of plants in the southern region of Gansu Province were higher than others. In the present study, the quality zones were identified and the influence paths of environmental factors were analyzed. Bangladesh J. Bot. 50(3): 763-773, 2021 (September) Special